Pengaruh Disiplin Kerja Dan Motivasi KerjaTerhadap Kualitas Layanan Pemerintah Daerah Kabupaten Pesawaran Lampung - Rahyono, Rahyono; Alansori, Apip (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2021)
Good service quality is important for the sustainability of an organization such as governmentbecause it will help the process of achieving goals, but if the quality of existing services is notbalanced with poor work habits it will also affect the quality of service itself. Therefore the qualityof service can also be influenced by work discipline. Motivation that exists in employees willmanifest a behavior that is directed at the goals in achieving the expected goals. So, motivation isnot something that can be observed but is something that can be concluded because of somethingvisible behavior. Motivation is also something that makes a person enthusiastic about doing work.The population in this study were employees of the Pesawaran District Government. The sample inthis study amounted to 135 government employees from eachagency in Pesawaran LampungRegency. The data collection technique used is literature study by reading literature, referencematerials, lecture materials, and other research results that are related to the object under studyand a questionnaire by asking anumber of questions in writing which are given to respondents.Data processing techniques use the computerized SPSS program (statistical package for socialsciences) version 20 for windows. The results of this study indicate that work discipline and workmotivation have an effect on the service quality of the Pesawaran District Government.Keywords: Work Discipline, Work motivation and Quality of Service